Reproductive characteristics of the big blue octopus, Octopus cyanea (Gray 1849) in Zanzibar coastal waters, Tanzania - Amini Ismail Hamad; Batuli Yahya; Edward Moto; Christopher Muhando (Western Indian Ocean Journal of Marine Science, 2025)
The big blue octopus, Octopus cyanea (Gray 1849) is heavily fished in Zanzibar coastal waters, yet several aspects of its biology remain unstudied in the area. The reproductive biology of O. cyanea (Gray 1849) was investigated, including sex ratios, length-weight relationships, size at maturity, and seasonal variation in maturity and spawning activity. Sampling of specimens caught by local fishers was conducted monthly at four sites. Octopus size and weight were measured and the sex determined, whereafter their gonads were extracted and staged. Female octopuses dominated the sex ratio across most size classes and seasons. Males reached sexual maturity at a smaller size than females and mature individuals of both sexes were present throughout the year, suggesting continuous spawning activity. Based on the gonadosomatic index (GSI), peak spawning periods were in June and October. The new insights into the reproductive dynamics of O. cyanea are important for fisheries management efforts and effective conservation of the species.

The influence of fishing methods on catch size, catch rate, and size distribution of Octopus cyanea (Gray, 1849) in Zanzibar, Tanzania - Amini I. Hamad; Christopher A. Muhando; Batuli M. Yahya (Fisheries Research, 2025)

A sustainable blue economy may not be possible in Tanzania without cutting emissions - Ana M. Queirós; Elizabeth Talbot; Flower E. Msuya; Baraka Kuguru; Narriman Jiddawi; Shigalla Mahongo; Yohana Shaghude; Christopher Muhando; Elias Chundu; Zoe Jacobs; Sevrine Sailley; Elina A. Virtanen; et al. (Science of The Total Environment, 2024)

Status and long-term changes of coral reefs around Zanzibar - Ali M. Ussi; Mohammed S. Mohammed; Rashid J. Rashid; Mohammed A. Sheikh; Peter A. Staehr; Christopher A. Muhando; Saleh Yahya; Karsten Dahl (Frontiers in Marine Science, 2024)
Introduction Coral reefs as key ecosystems in Zanzibar are exposed to several anthropogenic and natural stressors. Methods The benthic composition and coverage of coral reefs were investigated on three data sets involving ten coral reefs monitored from 1992 to 2016. Firstly, we investigated differences in the reef composition using data from seven reefs in 2015. Secondly, we analyzed communities on three distinctive reefs (2010 to 2012) to understand the importance of seasons and reef zones (slope, crest and flat) on species abundance. Finally, we investigated long-term changes (1992 to 2016) of five reefs. Results Branching Porites and Acropora , and soft coral order Corallimorpharia, characterized sheltered reef communities. Soft corals and algal species characterized the reef communities exposed to strong hydrodynamic conditions, which also displayed greater cover of rocks and rubbles. The average dissimilarity between reefs ranged between 60% and 75%. The seasonal changes in community structure for reefs near Stone Town were mostly associated with soft coral Corallimorpharia. Indeed, the bare rock and algae distinguished the northern exposed reef from more sheltered reefs. Acropora was a key genus for the sheltered Chumbe reef, which explained between 14% and 18% of the dissimilarities among the three reefs. Hard corals covered between 40% and 70% in most years, with severe declines following El Niño events in 1998 and 2016. The dominating genus Acropora showed a strong decline from the late 1990s’ with signs of recovery at remote reefs compared to reefs closer to human residence. Discussion Our results highlight the importance of seasonality and spatial differences, reflecting differences in human impact and physical exposure and significant long-term changes in coral communities. Continued monitoring of reef health is essential to evaluate the success of ongoing management to sustain the reef services.

Feeding habits and diet composition of Octopus cyanea (Gray, 1849) in Zanzibar waters, Tanzania - Amini I. Hamad; Christopher A. Muhando (Western Indian Ocean Journal of Marine Science, 2023)
The octopus fishery in Zanzibar is an essential activity of coastal communities. To assist with developing fisheries management plans, baseline information on the feeding of Octopus cyanea (Gray, 1849) was collected in relation to sex and maturity stages. The feeding habits and diet composition of 543 O. cyanea were studied over a period of 12 months at Paje, Kizimkazi, Chwaka Bay and Nungwi. Samples at each site were collected on two days per month during spring tide. Digestive tract contents revealed that O. cyanea preyed on 36 species of crustaceans, molluscs and fishes, with crabs a major prey item. The number of prey species in a single stomach ranged from one to six. O. cyanea in Zanzibar is therefore a generalist predator with a mixed diet. The octopus gonadosomatic index (GSI) indicated a peak breeding season in June to October, which correlated with low prey consumption. Mature octopuses ingested a small amount of food from mainly small sessile prey. Females consumed less food than males of similar maturity stages, suggesting that they ate less or had higher digestion rates. The information is useful for developing fisheries management plans for the octopus fishery in Zanzibar.

Mitochondrial DNA revealed a single stock structure of the Spotted sardinella Amblygaster sirm (Walbaum, 1792) (Teleostei; Clupeidae) in Tanzanian coastal waters - Godfrey Fabiani; Cretus Joseph Mtonga; Leonard Jones Chauka; Cyrus Rumisha; Christopher Adriano Muhando (Marine Biodiversity, 2023)

Supporting Spatial Management of Data-Poor, Small-Scale Fisheries With a Bayesian Approach - Jennifer Rehren; Maria Grazia Pennino; Marta Coll; Narriman Jiddawi; Christopher Muhando (Frontiers in Marine Science, 2021)
Marine conservation areas are an important tool for the sustainable management of multispecies, small-scale fisheries. Effective spatial management requires a proper understanding of the spatial distribution of target species and the identification of its environmental drivers. Small-scale fisheries, however, often face scarcity and low-quality of data. In these situations, approaches for the prioritization of conservation areas need to deal with scattered, biased, and short-term information and ideally should quantify data- and model-specific uncertainties for a better understanding of the risks related to management interventions. We used a Bayesian hierarchical species distribution modeling approach on annual landing data of the heavily exploited, small-scale, and data-poor fishery of Chwaka Bay (Zanzibar) in the Western Indian Ocean to understand the distribution of the key target species and identify potential areas for conservation. Few commonalities were found in the set of important habitat and environmental drivers among species, but temperature, depth, and seagrass cover affected the spatial distribution of three of the six analyzed species. A comparison of our results with information from ecological studies suggests that our approach predicts the distribution of the analyzed species reasonably well. Furthermore, the two main common areas of high relative abundance identified in our study have been previously suggested by the local fisher as important areas for spatial conservation. By using short-term, catch per unit of effort data in a Bayesian hierarchical framework, we quantify the associated uncertainties while accounting for spatial dependencies. More importantly, the use of accessible and interpretable tools, such as the here created spatial maps, can frame a better understanding of spatio-temporal management for local fishers. Our approach, thus, supports the operability of spatial management in small-scale fisheries suffering from a general lack of long-term fisheries information and fisheries independent data.

Variable thermal stress tolerance of the reef-associated symbiont-bearing foraminifera Amphistegina linked to differences in symbiont type - Marleen Stuhr; Achim Meyer; Claire E. Reymond; Gita R. Narayan; Vera Rieder; Jörg Rahnenführer; Michal Kucera; Hildegard Westphal; Christopher A. Muhando; Pamela Hallock (Coral Reefs, 2018)